2018
DOI: 10.1038/s41598-018-35111-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between one-carbon metabolism indices and DNA methylation status in maternal and cord blood

Abstract: One-carbon metabolism is essential for multiple cellular processes and can be assessed by the concentration of folate metabolites in the blood. One-carbon metabolites serve as methyl donors that are required for epigenetic regulation. Deficiencies in these metabolites are associated with a variety of poor health outcomes, including adverse pregnancy complications. DNA methylation is known to vary with one-carbon metabolite concentration, and therefore may modulate the risk of adverse pregnancy outcomes. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…In vascular disease, global DNA methylation was altered with a concomitant increase in plasma tHcy and SAH 34 . Of further interest, a recent study by Knight et al demonstrated that five out of thirteen 1C metabolites changed over pregnancy and these metabolites were associated with altered methylation levels of genes involved in neuronal and developmental process in both maternal and cord blood 23 . These findings add to the evidence that alteration in the indices of 1C metabolism in B12 deficient status could change the methylation potential, mediate the epigenetic modifications and contribute to adverse lipid levels and metabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vascular disease, global DNA methylation was altered with a concomitant increase in plasma tHcy and SAH 34 . Of further interest, a recent study by Knight et al demonstrated that five out of thirteen 1C metabolites changed over pregnancy and these metabolites were associated with altered methylation levels of genes involved in neuronal and developmental process in both maternal and cord blood 23 . These findings add to the evidence that alteration in the indices of 1C metabolism in B12 deficient status could change the methylation potential, mediate the epigenetic modifications and contribute to adverse lipid levels and metabolic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A Danish cross-sectional study in non-pregnant adults found that plasma 1C metabolites positively associated with higher risk of metabolic dysfunction 22 . In addition, a recent study of mother-infant dyads identified changes in methylation patterns in 993 CpG sites, which were related to altered 1C metabolite indices over pregnancy, thereby suggesting the impact of different 1C metabolites on regulation of DNA methylation at multiple sites 23 . This evidence supports that altered 1C metabolites, adversely affect epigenetic mechanisms and metabolic health of both mother and offspring.…”
Section: Sdmentioning
confidence: 99%
“…Correlations between maternal blood, cord blood metabolites (e.g., homocysteine, TMAO, 5meTHF, Vitamin B12, choline, methionine, SAH, etc.) and DNA methylation have been observed highlighting the key role of maternal metabolites in the modulation of the offspring’s epigenome [ 20 ]. Stress in utero and during early postnatal life, as well as childhood maltreatment, influence the hypothalamic–pituitary–adrenal axis resulting in fetal exposure to excess glucocorticoids [ 21 ].…”
Section: Epigenetic Programming During the First 1000 Days Of Lifementioning
confidence: 99%
“…For example, folate deficiency in early pregnancy results in dysregulated 1-C metabolism, as revealed by an overall lower DNA methylation level. The maternal CpG sites, whose methylation levels change as the pregnancy proceeds, are most likely influenced by alterations in maternal folate and one-carbon metabolite concentrations [ 66 ].…”
Section: Nutrient Deficiencies Alter Early Developmentmentioning
confidence: 99%